Modulation of the droplet spectrum by working pressure, adjuvants, and herbicides - Batista de Alvarenga, Cleyton; Natalino Rinaldi, Paula Cristina; Arantes Rodrigues da Cunha, João Paulo; Ferreira Paranaíba, Patrícia; Zampiróli, Renan; Oliveira Faria, Layanara; de Oliveira, Vanderson Fernandes (Revista Ceres, 2026)
The droplet spectrum is a crucial factor in optimizing herbicide efficacy and minimizing spray drift. This study evaluated the effects of working pressure (100 to 600 kPa) and six adjuvants on droplet size, both in the absence and presence of herbicides, using an air-induction nozzle (TTI 110015VP) and a particle analyzer. Higher working pressures reduced droplet size – measured as Dv0.1, Dv0.5 (volume median diameter), and Dv0.9, representing the diameters at which 10%, 50%, and 90% of the total spray volume consists of droplets of that size or smaller – and increased the volume percentage of fine droplets (V100), regardless of the adjuvant or herbicide. Adjuvants influenced the droplet spectrum, with Xtend Protect1 significantly reducing Dv0.9. However, the lowest relative span, indicating greater droplet size uniformity, was achieved by different adjuvants depending on the working pressure. A significant interaction between herbicides and adjuvants was observed, underscoring the need for a comprehensive analysis of these variables to optimize application quality. The addition of adjuvants and herbicides to the spray solution altered the correlations between droplet spectrum variables, emphasizing the importance of considering multiple factors in application decisions. Selecting the appropriate working pressure and adjuvant, along with a thorough analysis of the droplet spectrum, is essential for effective weed control, reducing spray drift, and ensuring environmental, applicator, and consumer safety.